Fractal cycles of sleep, a new aperiodic activity-based definition of sleep cycles - Rosenblum, Yevgenia; Jafarzadeh Esfahani, Mahdad; Adelhöfer, Nico; Zerr, Paul; Furrer, Melanie; Huber, Reto; Roest, Famke F; Steiger, Axel; Zeising, Marcel; Horváth, Csenge G; Schneider, Bence; Bódizs, Róbert; et al. (eLife, 2025)
Sleep cycles are defined as episodes of non-rapid eye movement (non-REM) sleep followed by an episode of REM sleep. Fractal or aperiodic neural activity is a well-established marker of arousal and sleep stages measured using electroencephalography. We introduce a new concept of ‘fractal cycles’ of sleep, defined as a time interval during which time series of fractal activity descend to their local minimum and ascend to the next local maximum. We assess correlations between fractal and classical (i.e. non-REM – REM) sleep cycle durations and study cycles with skipped REM sleep. The sample comprised 205 healthy adults, 21 children and adolescents and 111 patients with depression. We found that fractal and classical cycle durations (89±34 vs 90±25 min) correlated positively ( r =0.5, p<0.001). Children and adolescents had shorter fractal cycles than young adults (76±34 vs 94±32 min). The fractal cycle algorithm detected cycles with skipped REM sleep in 91–98% of cases. Medicated patients with depression showed longer fractal cycles compared to their unmedicated state (107±51 vs 92±38 min) and age-matched controls (104±49 vs 88±31 min). In conclusion, fractal cycles are an objective, quantifiable, continuous and biologically plausible way to display sleep neural activity and its cycles.